Idea of thin‐film beam splitters for two‐colour beamlines. (16th August 2019) - Abe, Hitoshi
Abstract : The idea to split a mixed beam of soft X‐rays and hard X‐rays on the same axis into different directions is presented. This will be useful in the design of two‐colour beamlines. Abstract : The idea to split soft X‐ray and hard X‐ray beams on the same axis into different directions is presented. A thin‐film beam splitter can serve this purpose. Performances of thin‐film beam splitters made of carbon and aluminium were examined. The idea of thin‐film beam splitters expands possibilities in the design of two‐colour beamlines.